Investigation Assessment of Opportunity-Based Entrepreneurial Skills'Acquisition of Students in Tertiary Institutions During ASUU strike - Nnaemeka Oguezue; Emmanuel Chibuike Nwune; Samson Onyeluka Chukwuedo (International Journal of Entrepreneurship and Sustainability Studies, 2023)
The study investigated the opportunity-based entrepreneurial skills acquisition of undergraduate students in public universities during industrial actions by ASUU in Nigeria. Three research questions and one hypothesis guided the study. A descriptive survey research design and a sample of 744 undergraduate students using a purposive sampling technique, were used for the study. The instrument used for the study was a questionnaire, which was subjected to validation and reliability test. Data were collected online using Google Forms. Mean, standard deviation, percentage, and Chi-Square statistical tools were used to analyze the collected data. The results revealed that faculty of education undergraduate students in Nnamdi Azikiwe University, Awka, Anambra State are not idle but are meaningfully engaged in the learning of diverse entrepreneurial skills during ASUU strikes. The study also revealed significant gender stereotyping among the students in favour of female students in the acquisition of entrepreneurial skills. It was recommended amongst others that male students should be reoriented to begin embracing Culinary/Art skills. On the other hand, female students should be encouraged to also embrace technical skills.